Evaluation of the effect of 2′-O-methyl, fluoro hexitol, bicyclo and Morpholino nucleic acid modifications on potency of GalNAc conjugated antisense oligonucleotides in mice. Issue 23 (15th December 2018) - Prakash, Thazha P.; Yu, Jinghua; Kinberger, Garth A.; Low, Audrey; Jackson, Michaela; Rigo, Frank; Swayze, Eric E.; Seth, Punit P.
Graphical abstract: Highlights: GalNAc conjugation improved potency of 2′- O -methyl Gapmer ASO 10-fold. Potency of FHNA Gapmer ASO improved 14-fold by GalNAc conjugation. LNA and cEt BNA ASO GalNAc conjugates showed similar activity in mice liver. GalNAc conjugation improved activity of ASOs designed to correct pre-mRNA splicing. Abstract: The potency of antisense oligonucleotide (ASO) drugs has significantly improved in the clinic after exploiting asialoglycoprotein receptor (ASGR) mediated delivery to hepatocytes. To further this technology, we evaluated the structure–activity relationships of oligonucleotide chemistry on in vivo potency of GalNAc-conjugated Gapmer ASOs. GalNAc conjugation improved potency of ASOs containing 2′- O -methyl (2′- O -Me), 3′-fluoro hexitol nucleic acid (FHNA), locked nucleic acid (LNA), and constrained ethyl bicyclo nucleic acid (cEt BNA) 10–20-fold compared to unconjugated ASOs. We further demonstrate that GalNAc conjugation improves activity of 2′- O -(2-methoxyethyl) (2′- O -MOE) and Morpholino ASOs designed to correct splicing of survival motor neuron ( SMN2 ) pre-mRNA in liver after subcutaneous administration. GalNAc modification thus represents a viable strategy for enhancing potency of ASO with diverse nucleic acid modifications and mechanisms of action for targets expressed in hepatocytes.